Association between the subclinical level of problematic internet use and habenula volume: a look at mediation effect of neuroticism - Toshiya Murai; Hironobu Fujiwara; Qi Dai; Halwa Zakia; Yusuke Kyuragi; Naoya Oishi; Yuzuki Ishikawa; Lichang Yao; Morio Aki (General Psychiatry)
Background Ongoing debates question the harm of internet use with the evolving technology, as many individuals transition from regular to problematic internet use (PIU). The habenula (Hb), located between the thalamus and the third ventricle, is implicated in various psychiatric disorders. In addition, personality features have been suggested to play a role in the pathophysiology of PIU.Aims This study aimed to investigate Hb volumetry in individuals with subclinical PIU and the mediating effect of personality traits on this relationship.Methods 110 healthy adults in this cross-sectional study underwent structural magnetic resonance imaging. Hb segmentation was performed using a deep learning technique. The Internet Addiction Test (IAT) and the NEO Five-Factor Inventory were used to assess the PIU level and personality, respectively. Partial Spearman’s correlation analyses were performed to explore the relationships between Hb volumetry, IAT and NEO. Multiple regression analysis was applied to identify personality traits that predict IAT scores. The significant trait was then treated as a mediator between Hb volume and IAT correlation in mediation analysis with a bootstrap value of 5000.Results Relative Hb volume was negatively correlated with IAT scores (partial rho=−0.142, p=0.009). The IAT score was positively correlated with neuroticism (partial rho=0.430, p<0.001) and negatively correlated with extraversion, agreeableness and conscientiousness (partial rho=−0.213, p<0.001; partial rho=−0.279, p<0.001; and partial rho=−0.327, p<0.001). There was a significant indirect effect of Hb volume on this model (β=−0.061, p=0.048, boot 95% confidence interval: −0.149 to −0.001).Conclusions This study uncovered a crucial link between reduced Hb volume and heightened PIU. Our findings highlight neuroticism as a key risk factor for developing PIU. Moreover, neuroticism was shown to mediate the relationship between Hb volume and PIU tendency, offering valuable insight into the complexities of this interaction.